The Relevance of Assessing Subjective Experiences of Skin Toxicity During Adjuvant Radiotherapy for Breast Cancer - Bottesi, Gioia; Stefanelli, Antonio; Ambroso, Giovanni; Baratto, Gianni; Carraro, Eleonora; Cristaudo, Agostino; Giuntoli, Laura; Maramaldi, Giada; Meneghin, Martino; Pozzati, Genny; Semenzato, Alessandra; Togni, Stefano; et al. (Frontiers in Oncology, 2021)
Purpose: Radiodermatitis is likely to be an inevitable side effect of radiotherapy (RT) but experiencing pain relief during RT might contribute making treatment more acceptable and less impairing. The current study aimed to assess the subjective perceptions and experiences of skin toxicity in a sample of women undergoing adjuvant RT for breast cancer. Methods: Eighty patients were randomly assigned to one out of two groups: treatment (i.e., a newly developed topical product) and control (i.e., standard-of-care). Patients underwent adjuvant RT for 3 weeks. Clinical assessment of radiodermatitis and self-reported levels of pain, relief, and perceptions of treatment response were collected at the initiation of RT (T1), during RT (T2 and T3), and 2 weeks after treatment completion (T4). To assess changes in skin-related QoL, a subgroup of patients completed the Padua Skin-Related QoL questionnaire at T0 (before the initiation of RT) and at T4. Results: A comparable timing of onset and severity of radiodermatitis during treatment was observed in both groups. The treatment group reported lower levels of pain and higher levels of relief compared to the control group when skin toxicity was at its highest levels (T2 and T3). Independent of the group, levels of perceived improvements in clinical status increased over time, whereas skin-related QoL worsened from T0 to T4. Conclusion: Current findings outline the relevance of integrating clinical evaluations of radiodermatitis with patients’ subjective experiences of skin toxicity in interventional studies. Moreover, they provide preliminary evidence about the soothing effect of a newly developed topical product, thus supporting its usefulness of as a supportive care.